An Apology for Feeling - Gadris, Stelios (Aisthesis, 2025)
In what follows I will try to establish the role feeling plays, primarily, in Kant’s worldly conception of philosophy – some remarks will refer to its role in theoretical philosophy as well. I will claim that it is through feeling that we are able to situate ourselves within the world both physical and human. Situating ourselves within the world entails a broadening of our horizon, first and far most geographically and then in thought, both contributing to our moving beyond or overcoming what is private, be that feeling or judgment, that is, moving beyond self-interest. From the bare feeling of existence to the feeling of differentiating the directions in space in the physical world, and, finally, to the feeling of reflection Kant shows how this broadening can and should take place, namely, by broadening our way of thinking.